Cu < 2 + >, Ta < 5 + > and F <-> co-doped TiO2 giant dielectric ceramic material and preparation method thereof
By co-doping TiO2 with Cu2+, Ta5+ and F-, the oxygen vacancy and local electrons are regulated, the shortcomings of existing TiO2-based giant dielectric ceramic materials in terms of frequency and temperature stability are solved, high dielectric constant and low dielectric loss are achieved, and their stability is improved.
Patent Information
- Application Number
- CN202411937899.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The existing TiO2-based giant dielectric ceramic materials have shortcomings in frequency and temperature stability, making it difficult to achieve good dielectric constant and low dielectric loss.
By co-doping TiO2 with Cu2+, Ta5+ and F-, the oxygen vacancies concentration and local electrons are regulated, and the high dielectric constant and low dielectric loss of the ceramic are achieved, and its frequency and temperature stability are improved.
It achieves high dielectric constant (up to 1130) and low dielectric loss (up to 0.04) of ceramics, and has high frequency and temperature stability, suitable for commercial applications.
Smart Images

Figure CN119874351A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of ceramic materials, and relates to giant dielectric ceramic materials, and specifically to a Cu 2+ 、 5+ and F - Co-doped TiO2 giant dielectric ceramic material and preparation method thereof. Background Art
[0002] With the rapid development of the electronics industry, multilayer ceramic capacitors (MLCC) are widely used in new energy vehicles, aerospace and other fields. Among them, giant dielectric materials are the most effective means to achieve device miniaturization, integration and high performance. At present, the research on giant dielectric materials mainly includes: CaCu3Ti4O 12 (CCTO), BaTiO3, SrTiO3, etc. However, the high dielectric loss of CCTO ceramics and the poor temperature stability of BaTiO3 and SrTiO3 ceramics limit their further application. At present, the research on TiO2-based giant dielectric ceramics mainly focuses on co-doping with different cations (donor and acceptor ions) to regulate the giant dielectric properties. Donor cations such as: V 5+ , Nb 5+ 、 5+ and W 6+ etc., acceptor cations such as Ag + 、Zn 2+ 、Al 3+ However, this strategy is difficult to achieve good frequency and temperature stability, which limits its commercial application. Summary of the invention
[0003] In view of the shortcomings of the prior art, the present invention aims to provide a Cu 2+ 、 5+ and F - Co-doped TiO2 giant dielectric ceramic material and preparation method thereof, through Cu 2+ 、 5+ and F - Co-doping TiO2 can simultaneously reduce the oxygen vacancy concentration and localize electrons, maintaining a high dielectric constant and low dielectric loss in the ceramic, giving it high frequency and temperature stability, a simple preparation process, high yield, good repeatability and low cost.
[0004] In order to achieve the above object, the present invention adopts the following technical solutions:
[0005] A Cu 2+ 、 5+ and F - Co-doped TiO2 giant dielectric ceramic material, the general structure is: (Cu 1 / 3 Ta 2 / 3 )0.1 Ti 0.9-x / 4 O 2-x F x , where the value of x is 0.04~0.064.
[0006] Preferably, the value of x is 0.052.
[0007] The present invention also protects a Cu 2+ 、 5+ and F - The preparation method of the co-doped TiO2 giant dielectric ceramic material comprises the following steps:
[0008] Step 1: According to the stoichiometric ratio, weigh the CuF2, Ta2O5, TiO2 and CuO powder raw materials respectively, put the weighed raw materials into a ball mill, and then dry, grind and sieve to obtain a raw material mixture;
[0009] Step 2: placing the raw material mixture into an alumina crucible, placing the crucible in a box furnace, pre-calcining at 900-1100° C. for 1-4 hours, then cooling to room temperature, and again ball milling, drying, grinding, and sieving to obtain pre-calcined powder;
[0010] Step 3: Press the pre-sintered powder into tablets and place them in a tube furnace. In a nitrogen atmosphere, heat the mixture from room temperature to 1200-1330°C, keep the temperature for 3-6 hours, and then cool the mixture to room temperature.
[0011] Step 4: Place the sintered sample in a box furnace, heat it from room temperature to 1000-1150℃ in air atmosphere, anneal it for 1-3h, and then cool it to room temperature to obtain Cu 2+ 、 5+ and F - Co-doped TiO2 giant dielectric ceramic materials.
[0012] Preferably, the ball milling in step 1 and step 2 is performed using zirconium oxide balls as grinding balls and deionized water as ball milling medium, and the mixture is fully mixed and ball milled for 6 to 9 hours.
[0013] Preferably, the drying in step 1 and step 2 is performed by placing the product in an oven at 80-100° C. for 24 hours.
[0014] Preferably, the grinding in step 1 and step 2 is performed by grinding in a mortar for 30 to 60 minutes.
[0015] Preferably, the sieving in step 1 and step 2 is through a 120-200 mesh sieve.
[0016] Preferably, the pre-sintered powder tablets described in step 3 are pre-pressed into cylindrical green bodies with a diameter of 8 mm using a grinding tool, and then cold isostatically pressed for 3 to 5 minutes at a pressure of 200 MPa in a cold isostatic press.
[0017] Compared with the prior art, the present invention has the following technical effects:
[0018] The present invention regulates the dielectric properties by co-doping anions and cations and takes into account good frequency and temperature stability, that is, a Ta 5+ and high electronegativity Cu 2+ 、F - (F - χ=3.98 >Cu 2+ χ=1.90 >Ti 4+ χ=1.54 ) co-doped TiO2 ceramics. This doping strategy is conducive to the effective doping substitution of doped ions; in which Cu is co-doped at the Ti site of the TiO2 system. 2+ / Ta 5+ Double doping, Cu 2+ and Ti 4+ The ionic radius is close to Cu 2+ As an acceptor doping, oxygen vacancies are generated to balance the charge. The highly electronegative Cu 2+ Easy to attract electrons, resulting in Cu 2+ +e→Cu + At the same time, F - and O 2- The ionic radius is close to O position for F - Doping reduces the oxygen vacancy concentration and provides electrons, Cu 2+ and F - The large electronegativity of is beneficial to localized electrons and inhibits the long-range motion of electrons. 1 / 3 Ta 2 / 3 ) 0.1 Ti 1.887 O 1.948 F 0.052 The ceramic dielectric constant reaches 1130, the loss is kept at 0.04, and the temperature stability reaches X9F; it provides a new idea for the development of TiO2-based giant dielectric ceramics;
[0019] The preparation method of the invention has simple process, high yield, good repeatability and low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 XRD patterns of samples prepared in Examples 1 to 3 and Comparative Example 1;
[0021] Figure 2The curves of dielectric constant and dielectric loss versus frequency at room temperature of 1 kHz for samples prepared in Examples 1 to 3 and Comparative Example 1;
[0022] Figure 3 The temperature stability spectra of the samples prepared in Examples 1 to 3 and Comparative Example 1 at 1 kHz. DETAILED DESCRIPTION
[0023] The specific contents of the present invention are further explained in detail below in conjunction with embodiments.
[0024] Example 1
[0025] Step 1: According to (Cu 1 / 3 Ta 2 / 3 ) 0.1 Ti 0.887 O 1.948 F 0.052 According to the stoichiometric ratio, 0.1315 g of CuO with a purity of 99.9%, 3.3181 g of Ta2O5 with a purity of 99.99%, 15.9578 g of TiO2 with a purity of 99.99%, and 0.5976 g of CuF2 with a purity of 99.5% were weighed respectively, put into a nylon jar, and milled for 6 h in a ball mill at a speed of 400 r / min using zirconium balls as grinding balls and deionized water as ball milling media, dried at 80°C for 24 h, ground in a mortar for 30 min, and passed through a 120-mesh sieve to obtain a raw material mixture;
[0026] Step 2: Place the raw material mixture in an alumina crucible, compact it with an agate rod, cover it, place it in a box furnace, and heat it from room temperature to 1030°C at a heating rate of 5°C / min in an air atmosphere, keep it warm for 2 hours, cool it to 500°C at a cooling rate of 5°C / min, cool it naturally to room temperature with the furnace, take it out of the furnace, use a ball mill with a speed of 400r / min for 6 hours, place it in a drying oven at 80°C for 24 hours, grind it with a mortar for another 30 minutes, and pass it through a 120-mesh sieve to obtain a pre-calcined powder;
[0027] Step 3: Place the pre-sintered powder into a stainless steel mold with a diameter of 8 mm, press it into a cylindrical body without pressure using a powder tablet press, place the cylindrical body in a cold isostatic press, and cold isostatic press for 3 minutes at a pressure of 200 MPa; place the cylindrical body on a zirconia zirconium plate, place the zirconia zirconium plate in a tubular furnace, introduce nitrogen, heat it to 1290°C at a heating rate of 5°C / min, keep it warm for 4 hours, cool it to 500°C at a cooling rate of 5°C / min, and naturally cool it to room temperature with the furnace;
[0028] Step 4: Place the sintered sample in a box furnace, heat it from room temperature to 1090°C at a heating rate of 5°C / min for annealing for 2h in an air atmosphere, cool it to 500°C at a cooling rate of 5°C / min, and cool it naturally to room temperature to obtain Cu 2+ 、 5+ and F - Co-doped TiO2 giant dielectric ceramic materials.
[0029] Example 2
[0030] Step 1, according to (Cu 1 / 3 Ta 2 / 3 ) 0.1 Ti 0.89 O 1.96 F 0.04 0.2388 g of CuO with a purity of 99.9%, 3.3140 g of Ta2O5 with a purity of 99.99%, 15.9924 g of TiO2 with a purity of 99.99%, and 0.4592 g of CuF2 with a purity of 99.5% were weighed respectively in a nylon jar, and milled for 8 h in a ball mill at a speed of 400 r / min using zirconium balls as grinding balls and deionized water as ball milling media, dried at 100°C for 24 h, ground in a mortar for 60 min, and passed through a 200-mesh sieve to obtain a raw material mixture;
[0031] Step 2: Place the raw material mixture in an alumina crucible, compact it with an agate rod, cover it, place it in a box furnace, and heat it from room temperature to 900°C at a heating rate of 5°C / min in an air atmosphere, keep it warm for 4 hours, cool it to 500°C at a cooling rate of 5°C / min, cool it naturally to room temperature with the furnace, take it out of the furnace, use a ball mill with a speed of 400r / min for 8 hours, place it in a drying oven at 100°C for 24 hours, grind it with a mortar for another 60 minutes, and pass it through a 200-mesh sieve to obtain a pre-calcined powder;
[0032] Step 3: Place the pre-burned powder into a stainless steel mold with a diameter of 8 mm, press it into a cylindrical body without pressure using a powder tablet press, place the cylindrical body into a cold isostatic press, and cold isostatic press for 5 minutes at a pressure of 200 MPa; place the cylindrical body on a zirconia plate, place the zirconia plate in a tubular furnace, introduce nitrogen and heat the temperature to 1280°C at a heating rate of 5°C / min, keep warm for 6 hours, cool the temperature to 500°C at a cooling rate of 5°C / min, and naturally cool to room temperature with the furnace.
[0033] Step 4: Place the sintered sample in a box furnace, heat it from room temperature to 1050°C at a heating rate of 5°C / min for annealing for 3h in an air atmosphere, cool it to 500°C at a cooling rate of 5°C / min, and cool it naturally to room temperature to obtain Cu 2+、 5+ and F - Co-doped TiO2 giant dielectric ceramic materials.
[0034] Example 3
[0035] Step 1, according to (Cu 1 / 3 Ta 2 / 3 ) 0.1 Ti 0.884 O 1.936 F 0.064 0.0239 g of CuO with a purity of 99.9%, 3.3221 g of Ta2O5 with a purity of 99.99%, 15.9231 g of TiO2 with a purity of 99.99%, and 0.7365 g of CuF2 with a purity of 99.5% were weighed respectively in a nylon jar, and milled for 6 h in a ball mill at a speed of 400 r / min using zirconium balls as grinding balls and deionized water as ball milling media, dried at 90°C for 24 h, ground in a mortar for 40 min, and passed through a 150-mesh sieve to obtain a raw material mixture;
[0036] Step 2: Place the raw material mixture in an alumina crucible, compact it with an agate rod, cover it, place it in a box furnace, and heat it from room temperature to 1100°C at a heating rate of 5°C / min under air atmosphere, keep it warm for 1h, cool it to 500°C at a cooling rate of 5°C / min, cool it naturally to room temperature with the furnace, take it out of the furnace, use a ball mill with a speed of 400r / min for 6h, place it in a drying oven at 90°C for 24h, grind it with a mortar for another 40min, and pass it through a 150-mesh sieve to obtain a pre-calcined powder;
[0037] Step 3: Place the pre-burned powder into a stainless steel mold with a diameter of 8 mm, press it into a cylindrical body without pressure using a powder tablet press, place the cylindrical body into a cold isostatic press, and cold isostatic press for 4 minutes at a pressure of 200 MPa; place the cylindrical body on a zirconia plate, place the zirconia plate in a tubular furnace, introduce nitrogen and heat the temperature to 1330°C at a heating rate of 5°C / min, keep warm for 3 hours, cool the temperature to 500°C at a cooling rate of 5°C / min, and cool naturally to room temperature with the furnace.
[0038] Step 4: Place the sintered sample in a box furnace, heat it from room temperature to 1150°C at a heating rate of 5°C / min for annealing for 1h, cool it to 500°C at a cooling rate of 5°C / min, and cool it naturally to room temperature to obtain Cu 2+ 、 5+ and F - Co-doped TiO2 giant dielectric ceramic materials.
[0039] Example 4
[0040] Step 1: According to (Cu 1 / 3 Ta 2 / 3 ) 0.1 Ti 0.887 O 1.950 F 0.050 According to the stoichiometric ratio, 0.1315 g of CuO with a purity of 99.9%, 3.3181 g of Ta2O5 with a purity of 99.99%, 15.9578 g of TiO2 with a purity of 99.99%, and 0.5976 g of CuF2 with a purity of 99.5% were weighed respectively, put into a nylon jar, and milled for 6 h in a ball mill at a speed of 400 r / min using zirconium balls as grinding balls and deionized water as ball milling media, dried at 80°C for 24 h, ground in a mortar for 30 min, and passed through a 120-mesh sieve to obtain a raw material mixture;
[0041] Step 2: Place the raw material mixture in an alumina crucible, compact it with an agate rod, cover it, place it in a box furnace, and heat it from room temperature to 1000°C at a heating rate of 5°C / min in an air atmosphere, keep it warm for 2 hours, cool it to 500°C at a cooling rate of 5°C / min, cool it naturally to room temperature with the furnace, take it out of the furnace, use a ball mill with a speed of 400r / min for 6 hours, place it in a drying oven at 80°C for 24 hours, grind it with a mortar for another 30 minutes, and pass it through a 120-mesh sieve to obtain a pre-calcined powder;
[0042] Step 3: Place the pre-sintered powder into a stainless steel mold with a diameter of 8 mm, press it into a cylindrical body without pressure using a powder tablet press, place the cylindrical body in a cold isostatic press, and cold isostatic press for 3 minutes at a pressure of 200 MPa; place the cylindrical body on a zirconia zirconium plate, place the zirconia zirconium plate in a tubular furnace, introduce nitrogen, heat it to 1200°C at a heating rate of 5°C / min, keep it warm for 4 hours, cool it to 500°C at a cooling rate of 5°C / min, and naturally cool it to room temperature with the furnace;
[0043] Step 4: Place the sintered sample in a box furnace, heat it from room temperature to 1000°C at a heating rate of 5°C / min for annealing for 2h, cool it to 500°C at a cooling rate of 5°C / min, and cool it naturally to room temperature to obtain Cu 2+ 、 5+ and F - Co-doped TiO2 giant dielectric ceramic materials.
[0044] Comparative Example 1
[0045] Step 1, according to (Cu 1 / 3 Ta 2 / 3 ) 0.1 Ti 0.9The stoichiometric ratio of O2 was 99.9% pure CuO 0.5947g, 99.99% pure Ta2O5 3.3007g, and 99.99% pure TiO2 16.1071g, respectively, and they were put into a nylon jar, and milled for 6h in a ball mill at a speed of 400r / min using zirconium balls as grinding balls and deionized water as ball milling media, and dried at 80°C for 24h, and ground in a mortar for 30min and passed through a 120-mesh sieve to obtain a raw material mixture;
[0046] Step 2: Place the raw material mixture in an alumina crucible, compact it with an agate rod, cover it, place it in a box furnace, and heat it from room temperature to 1030°C at a heating rate of 5°C / min in an air atmosphere, keep it warm for 2 hours, cool it to 500°C at a cooling rate of 5°C / min, cool it naturally to room temperature with the furnace, take it out of the furnace, use a ball mill with a speed of 400r / min for 6 hours, place it in a drying oven at 90°C for 24 hours, grind it with a mortar for another 30 minutes, and pass it through a 120-mesh sieve to obtain a pre-calcined powder;
[0047] Step 3: Place the pre-burned powder into a stainless steel mold with a diameter of 8 mm, press it into a cylindrical body without pressure using a powder tablet press, place the cylindrical body into a cold isostatic press, and cold isostatic press for 4 minutes at a pressure of 200 MPa; place the cylindrical body on a zirconia plate, place the zirconia plate in a tubular furnace, introduce nitrogen, heat up to 1200°C at a heating rate of 5°C / min, keep warm for 4 hours, cool to 500°C at a cooling rate of 5°C / min, and naturally cool to room temperature with the furnace.
[0048] Step 4: Place the sintered sample in a box furnace, heat it from room temperature to 1000°C at a heating rate of 5°C / min for annealing for 2h, cool it to 500°C at a cooling rate of 5°C / min, and cool it naturally to room temperature to obtain Cu 2+ 、 5+ Co-doped TiO2 giant dielectric ceramic materials.
[0049] Figure 1 XRD patterns of samples prepared in Examples 1 to 3 and Comparative Example 1; Figure 1 It can be seen that the main phase of all samples is a pure rutile TiO2 phase structure, which means that Examples 1 to 3 and Comparative Example 1 prepared ceramic samples with rutile TiO2 as the main phase.
[0050] Figure 2 The curves of dielectric constant and dielectric loss versus frequency at room temperature of 1 kHz for samples prepared in Examples 1 to 3 and Comparative Example 1; Figure 2 It can be seen that when x=0.052, its dielectric constant is 1130 and the loss is 0.04.
[0051] Figure 3 The temperature stability spectra of the samples prepared in Examples 1 to 3 and Comparative Example 1 at 1 kHz; Figure 3 It can be seen that when x = 0.052, X9F(Δε r / ε 25 ℃: -55℃-200℃≤±7.5%) for practical application; when x=0.04, it meets the temperature stability of X9P (Δεr / ε25℃: -55℃-200℃Δ±10%).
[0052] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A Cu 2+ 、 5+ and F - Co-doped TiO2 giant dielectric ceramic material, characterized in that: The general structural formula is: (Cu 1 / 3Ta 2 / 3 ) 0.1 Ti 0.9-x / 4 O 2-x F x , where the value of x is 0.04~0.
064.
2. Cu as claimed in claim 1 2+ 、 5+ and F-co-doped TiO2 giant dielectric ceramic material, characterized in that, The value of x is 0.
052.
3. A Cu as claimed in claim 1 or 2 2+ 、 5+ and F - The method for preparing a co-doped TiO2 giant dielectric ceramic material is characterized in that: The following steps are involved: Step 1: According to the stoichiometric ratio, weigh the CuF2, Ta2O5, TiO2 and CuO powder raw materials respectively, put the weighed raw materials into a ball mill, and then dry, grind and sieve to obtain a raw material mixture; Step 2: placing the raw material mixture into an alumina crucible, placing the crucible in a box furnace, pre-calcining at 900-1100° C. for 1-4 hours, then cooling to room temperature, and again ball milling, drying, grinding, and sieving to obtain pre-calcined powder; Step 3: Press the pre-sintered powder into tablets and place them in a tube furnace. In a nitrogen atmosphere, heat the mixture from room temperature to 1200-1330°C, keep the temperature for 3-6 hours, and then cool the mixture to room temperature. Step 4: Place the sintered sample in a box furnace, heat it from room temperature to 1000-1150℃ in air atmosphere, anneal it for 1-3h, and then cool it to room temperature to obtain Cu 2+ 、 5+ and F - Co-doped TiO2 giant dielectric ceramic materials.
4. Cu as claimed in claim 3 2+ 、 5+ and F - The method for preparing a co-doped TiO2 giant dielectric ceramic material is characterized in that: The ball milling described in step 1 and step 2 uses zirconium oxide balls as grinding balls and deionized water as ball milling medium, and the mixture is fully mixed and ball milled for 6 to 9 hours.
5. Cu as claimed in claim 3 2+ 、 5+ and F - The method for preparing a co-doped TiO2 giant dielectric ceramic material is characterized in that: The drying in step 1 and step 2 is performed by placing the product in an oven at 80-100° C. for 24 hours.
6. Cu as claimed in claim 3 2+ 、 5+ and F - The method for preparing a co-doped TiO2 giant dielectric ceramic material is characterized in that: The grinding described in step 1 and step 2 is performed by grinding in a mortar for 30 to 60 minutes.
7. Cu as claimed in claim 3 2+ 、 5+ and F - The method for preparing a co-doped TiO2 giant dielectric ceramic material is characterized in that: The sieving in step 1 and step 2 is through a 120-200 mesh sieve.
8. Cu as claimed in claim 3 2+ 、 5+ and F - The method for preparing a co-doped TiO2 giant dielectric ceramic material is characterized in that: The pre-sintered powder tablets described in step 3 are pre-pressed into cylindrical green bodies with a diameter of 8 mm using a grinding tool, and then cold isostatically pressed for 3 to 5 minutes at a pressure of 200 MPa in a cold isostatic press.
Citation Information
Patent Citations
Ceramic dielectric film for capacitor and preparation method and application thereof
CN109608189A
CuO and Ta2O5 codoped rutile ceramic material and preparation method
CN109761600A
Nitrogen and oxygen vacancy double-doped titanium dioxide quantum dot photocatalyst as well as preparation method and application thereof
CN118079890A
Giant dielectric constant material
US20140293506A1
Ceramic material and method for preparing the same
US20200189980A1